2021
DOI: 10.1016/j.aninu.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing N-carbamoylglutamate in late gestation increases newborn calf weight by enhanced placental expression of mTOR and angiogenesis factor genes in dairy cows

Abstract: The objective of this study was to investigate whether supplementation with N -carbamoylglutamate (NCG) to cows during late gestation alters uteroplacental tissue nutrient transporters, calf metabolism and newborn weight. Thirty multiparous Chinese Holstein cows were used in a randomized complete block design experiment. During the last 28 d of pregnancy, cows were fed a diet without (CON) or with NCG (20 g/d per cow). The body weight of calves was weighed immediately after birth. Placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, supplementation of nutritionally restricted (50% NRC) single-bearing ewes from 100 to 125 dga with Arg also failed to elicit a fetal growth or placental development effect [ 30 ]. In contrast, when animals are fed to meet or exceed nutritional requirements, NCG supplementation during the last 28 dga in cattle [ 22 ], or Arg supplementation from 100 dga to term in twin-bearing ewes [ 10 ], has been reported to have a positive effect on fetal growth. Collectively, these results suggest that the level of nutritional restriction on the ewes in the present study may have been too severe to be rescued by NCG supplementation in mid-late gestation, when the nutritional requirements are the greatest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, supplementation of nutritionally restricted (50% NRC) single-bearing ewes from 100 to 125 dga with Arg also failed to elicit a fetal growth or placental development effect [ 30 ]. In contrast, when animals are fed to meet or exceed nutritional requirements, NCG supplementation during the last 28 dga in cattle [ 22 ], or Arg supplementation from 100 dga to term in twin-bearing ewes [ 10 ], has been reported to have a positive effect on fetal growth. Collectively, these results suggest that the level of nutritional restriction on the ewes in the present study may have been too severe to be rescued by NCG supplementation in mid-late gestation, when the nutritional requirements are the greatest.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact on fetal growth and development after 110 days of gestation in sheep has not been reported. One study in dairy cows suggests that maternal supplementation with NCG during the last 28 days of pregnancy improved the newborn weight via improvement of angiogenesis, nutrient transport and urea cycle in the fetus [ 22 ]. It is not clear if a similar time of intervention in pregnant sheep would improve the fetal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al [ 72 ] reported that dietary supplementation of multiparous Chinese Holstein dairy cows in the last 28 d of gestation increased newborn calf weight by ~ 5 kg which may have been mediated at least in part by enhanced placental expression of mTOR (a key regulator of nutrient transport) and angiogenic factors to enhance nutrient supply to the fetus. Supplementation with NCG from 0–90 d gestation in goats increases circulating Arg concentrations and may improve brown adipose tissue development [ 67 ].…”
Section: Ncg and Ruminant Reproductionmentioning
confidence: 99%
“…The fetus exchanges substances with the mother mainly through the placental blood circulation system, obtaining nutrients and excreting metabolic wastes ( 17 ). As the interface between mother and fetus, the placenta can transport important nutrients, such as glucose (GLU), amino acid and fatty acid, from mother to fetus by specific transporters ( 18 ). Higher expressions of nutrient transporters in the placenta are beneficial for nutrients transport, which have important effects on the healthy development of fetus ( 19 ).…”
Section: Introductionmentioning
confidence: 99%